Exploring the Role of Lecturers' Psychological Readiness, Teaching Expertise, and Perceptions in Advancing Digital Literacy Integration in Higher Education: - Mardiana, Harisa (EDUJ : English Education Journal, 2024)
Exploring the Integration of Digital Literacy (DL) in Higher Education (PT) is a complex and continuously developing relationship. This research aims to identify barriers and factors for effective integration and assess their impact on learning. This research uses mixed methods to measure 93 lecturers from various academic backgrounds, and teaching experiences to reveal the multifaceted dynamics of DL integration by examining experiences, perceptions, and institutional factors that influence lecturers. Correlation findings reveal distinct relationships, while regression and structural equation modeling highlight the explanatory power of selected predictors. The findings of this research have practical implications for lecturers, administrators, and policymakers in higher education. Additionally, this research contributes to the scholarly discourse by capturing diverse narratives surrounding the integration of DL in HE. This increased understanding of research opens up opportunities for future research in the form of further investigation into the specific dynamics of peer influence and the impact of institutional policies. In conclusion, higher education institutions adapt to the digital era's demands, and collective research and practice efforts can form an inclusive and adaptive education system.